Segment Reporting Level And Analyst Forecast Accuracy - Heo, Kyongsun; Doo, Seoyoung (Journal of Applied Business Research, 2018)
In a setting where the primary financial statements have been converted from individual financial statements to consolidated financial statements in Korea, we examine the effect of segment information disclosed by the firm on analysts’ consolidated-base earnings forecast accuracy. Since Korean firms have prepared the primary financial statements on a non-consolidated basis in the pre-IFRS regime, the adoption of International Financial Reporting Standards (IFRS) leads to a great deal of difficulties and complexities in making accurate consolidated forecasts for users of financial statements, even for financial analysts who are sophisticated users of financial statements. In this situation, we conjecture that the amount of details and types of information in segment disclosure will influence analysts’ forecast accuracy. Consistent with the prediction, we find that financial analysts are able to make more accurate earnings projections when firms provide more disaggregated accounting figures by each segment. Moreover, we find that analysts can make forecasts more accurately when firms disclose more persistent earnings component (i.e., segment operating income). Furthermore, we find that the effect of the segment disclosure levels on analysts’ forecast accuracy is more pronounced for firms with multi-segments. Our results indicate that disaggregated segment information is a useful source for financial analysts to have better understanding about complete picture of firms’ consolidated earnings and improve their forecasting performance.
Keywords: IFRS; Segment Reporting; Consolidated Financial Statements; Analyst Forecast Accuracy